New palaeomagnetic results from Late Paleozoic volcanic units along the western Gondwana margin in La Pampa, Argentina - Tomezzoli, Renata Nela; Saint Pierre, Teresa; Valenzuela, Claudia (Earth, Planets and Space)
Preliminary palaeomagnetic results from the Paleozoic volcanic units along the Gondwana margin in Argentina are presented. Even though we are still working on the palaeomagnetic data of the sampled section, these data are consistent with data from former studies carried out in the area. More than 90 specimens were measured from the Sierra Chica locality (37°52′S; 65°27′W) computed in 11 sites (Sc1-Sc11). These rocks are carriers of a characteristic remanence magnetization with reverse polarity, acquired during the Early Permian and assigned to the Kiaman Superchron. The resulting palaeomagnetic pole (PP) is Lat.: 64°S; Long.: 017°E, A95 = 15°, K = 12, N = 10. Others interpretations are also possible if the directions of two sites (SC9 and SC10) are considered to have a different magnetic field record, In that case, the PP calculated for sites Sc1-Sc7 is Lat.: 65°S; Long.: 44°E, A95 = 8°, K = 54, N = 7, and the virtual geomagnetic pole (VGP) calculated for sites Sc9 and Sc10 is Lat.: 48.5°S; Long.: 315°E, A95 = 8°, N = 2. The last possibility to consider Sc9 and Sc10 after structural correction, and the resulting PP position is Lat.: 66.5°S; Long.: 034°E, A95 = 8°, K = 41, N = 9. This deformation episode could be related to the San Rafaelic orogenic phase, found for the first time in La Pampa province, but previously observed in other neighboring areas during Permian time. However, more detailed palaeomagnetic sampling, rock magnetism studies, and age dating are necessary to complete the palaeomagnetic study of this area. Fil: Tomezzoli, Renata Nela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Saint Pierre, Teresa. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina Fil: ...